2000
DOI: 10.1002/(sici)1522-2675(20000510)83:5<995::aid-hlca995>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR Analysis of Intra- and Intermolecular H-Bonds of Alcohols in DMSO: Chemical Shift of Hydroxy Groups and Aspects of Conformational Analysis of Selected Monosaccharides, Inositols, and Ginkgolides

Abstract: The interpretation of 1H‐NMR chemical shifts, coupling constants, and coefficients of temperature dependence (δ(OH), J(H,OH), and Δδ(OH)/ΔT values) evidences that, in (D6)DMSO solution, the signal of an OH group involved as donor in an intramolecular H‐bond to a hydroxy or alkoxy group is shifted upfield, whereas the signal of an OH group acting as acceptor of an intramolecular H‐bond and as donor in an intermolecular H‐bond to (D6)DMSO is shifted downfield. The relative strength of the intramolecular H‐bond d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…In many interesting systems, the available chemical shift range is much smaller; as one example, the total hydrogen chemical shift range for various carbohydrates like cellulose or starch or chitin but also simple sugars [19][20][21][22] is in the order of one ppm. In this paper we extend the 2 H MAS methodology to systems with small chemical-shift differences.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…In many interesting systems, the available chemical shift range is much smaller; as one example, the total hydrogen chemical shift range for various carbohydrates like cellulose or starch or chitin but also simple sugars [19][20][21][22] is in the order of one ppm. In this paper we extend the 2 H MAS methodology to systems with small chemical-shift differences.…”
Section: Introductionsupporting
confidence: 52%
“…FT-IR spectroscopy provided indication that two of the possible three (on C2, C3, and C6 carbons) exchangeable hydroxyl groups [34,35] that may get exchanged. In liquid state, the chemical shift difference [19][20][21][22] between those peaks is small and its variation with, for example, solvent is comparable to its value. As concerning the magnitudes of their quadrupole coupling, there is no prior data available; the only related (though, not directly comparable) data are the C-H bond order parameters obtained from residual 13 C-1 H dipole-dipole couplings which show a rather small or negligible (depending on the source of cellulose) difference between C6 residues on one hand and C-2,3 residues on the other hand [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect could also be augmented by intramolecular H-bonding between the hydrogen of the OH on C 2 and the oxygen of the aglycon in the methyl-a-glycosides. The latter conclusion is supported by proton nuclear magnetic resonance ( 1 H NMR) studies of a-and b-methyl-gluco-and galactosides in DMSO, where it was found that the coupling constant J(H,OH) and the chemical shift d(OH) for the hydroxyl group at C 2 were larger for methyl-a-glucoside and methyl-a-galactoside than for their b counterparts (Bernet & Vasella, 2000). The same study showed that, in DMSO, the DJ(H,OH) and Dd(OH) between a-and b-methyl-galactosides (again for the OH at C 2 ) were both larger than the corresponding differences between a-and bmethyl-glucosides, and ranked these four glycosides in the order b-MeGlc > b-MeGal > a-MeGlc > a-MeGal with respect to chemical shift at the C 2 OH.…”
Section: Solution Conformational Entropies In Dmac and Dmac/liclmentioning
confidence: 99%
“…Vasella and co-workers 24,25 investigated the intramolecular hydrogen bonding in 4 by an analysis of their FT-IR spectra in CCl 4 and DMSO solutions. A strong intramolecular hydrogen bond was observed between the C6-hydroxyl group and the oxygen atom O4 (O6-H69 … O4) while the C2-OH group exhibited weaker hydrogen bonding with the orthoester oxygen atoms O1 and O3 in solution.…”
Section: Resultsmentioning
confidence: 99%